ifo World Economic Survey November 2019 - Dorine Boumans; Friedrich Schneider (ifo World Economic Survey, 2019)
World Economic Climate: The ifo World Economic Climate Has Worsened Again Advanced Economies: Confidence in Advanced Economies Deteriorates Further Emerging and Developing Economies: Economic Performance in Emerging Markets and Developing Economies Reaches Lowest Level Since 2009 Special Question: The Size and Impact of the Shadow Economy Worldwide and in Regions
Keywords: 330